Development and characterization of a microemulsion system containing amphotericin B with potential ocular applications - Da Silveira, Walteçá Louis Lima; Damasceno, Bolivar P. G. L.; Ferreira, Laura F.; Ribeiro, Izabel L. S.; Silva, Karolyne S.; Silva, André Leandro; Giannini, Maria José Mendes [UNESP]; Da Silva-Júnior, Arnóbio Antônio; De Oliveira, Anselmo Gomes [UNESP]; Do Egito, E. Sócrates Tabosa (Bentham Science Publishers, 2015)
Background: Amphotericin B eye drops are widely used in the treatment of ocular infections. However, amphotericin’s toxicity leads to low patient compliance and aggravation of symptoms. This work describes the development of a microemulsion system containing amphotericin B, aiming for its use in ocular applications. Methods: The microemulsion was developed by the titration technique. The physicochemical characteristics were determined with both loaded and unloaded amphotericin B-microemulsion. The nanostructures were analyzed by polarized light microscopy. The microdilution method was used to establish the minimum inhibitory concentration against fungal strains, and, therefore, evaluate the microemulsion activity. Additionally, in order to evaluate the microemulsion toxicity an in vitro toxicity assay against red blood cells was performed. Results: The performed studies showed that the presence of amphotericin B loaded into the system did not induce serious changes in the physicochemical properties of the microemulsion when compared to the unloaded system. The spectrophotometric studies depicted amphotericin B-self-associated species, which allow predicting its behavior in vitro. The high pressure liquid chromatography results revealed high drug content entrapment in the microemulsion droplet. Finally, the amphotericin B-microemulsion in vitro susceptibility test showed high activity against Candida strains and a low toxicity profile against red blood cells when compared to Fungizone®. Conclusion: The physicochemical characterization of the microemulsion demonstrated that its characteristics are compatible with the topical ocular route, making it eligible for consideration as a new and interesting amphotericin B-deliverydosage form to be used as eye drop formulation.
Keywords: Amphotericin B; Drug carriers; Eye drops; Microemulsions; Pharmaceutical nanotechnology; Red blood cells